The Effectiveness of Quizlet.com in Arabic Vocabulary Learning; Students’ Perception and Acceptance of Technology - Muhammad Nur Kholis; Muhammad Fahrun Nadhif (IAIN Salatiga, 2023)
The increasingly massive development of technology makes language learning no longer limited to only being in the classroom, but can be done anywhere using digital devices. Vocabulary is one of the important parts of language acquisition because vocabulary is the initial stage of mastering the four language skills. This study aims to determine the influence of the use of Quizlet in mastering the Arabic vocabulary of Arabic Language and Literature students, student perceptions of the use of the application in learning Arabic vocabulary, and acceptance of the technology used in quizlet.com. This study used an experimental design and was conducted on 25 Arabic Language and Literature students. This study used several data collection techniques, including pretest-posttest, perception questionnaires, and Technology Acceptance Model (TAM) questionnaires. The results of this study explained that the value of the posttest was greater than the pretests and the results of the T-Test showed a significant difference. These results are supported by a perception questionnaire that shows that students consider the use of the quizlet.com application to be effectively used in learning Arabic vocabulary. As well as the results of the TAM questionnaire showed that students were satisfied with the use of quizlet.com in learning Arabic vocabulary. The results of this study can be a recommendation for Arabic teachers, that quizlet.com can be used as a medium for learning Arabic vocabulary both in the classroom and outside the classroom.